2022
DOI: 10.1177/21925682221137823
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence, Characteristics and Outcomes of Vertebral Artery Injury Associated with Cervical Spine Trauma: A Systematic Review

Abstract: Study design Systematic Review Objectives Vertebral Artery Injury (VAI) is a potentially serious complication of cervical spine fractures. As many patients can be asymptomatic at the time of injury, the identification and diagnosis of VAI can often prove difficult. Due to the high rates of morbidity and mortality associated with VAI, high clinical suspicion is paramount. The purpose of this review is to elucidate incidence, diagnosis, treatment and outcomes of VAI associated with cervical spine injuries. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Other less frequently reported fracture types included burst fractures, Hangman fractures, Jefferson fractures, subaxial fractures, lateral mass fractures, lamina fractures, pedicle fractures, arch fractures, and ligamentous injuries. 3 , 46 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other less frequently reported fracture types included burst fractures, Hangman fractures, Jefferson fractures, subaxial fractures, lateral mass fractures, lamina fractures, pedicle fractures, arch fractures, and ligamentous injuries. 3 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Other less frequently reported fracture types included burst fractures, Hangman fractures, Jefferson fractures, subaxial fractures, lateral mass fractures, lamina fractures, pedicle fractures, arch fractures, and ligamentous injuries. 3,46 Studies have shown that a significant percentage (70%) of cases involving VAI after cervical spine trauma exhibit neurological symptoms within the first 24 hours. However, there have been instances where there was a delay of up to 18 hours between the injury and the onset of neurological symptoms in 44% of cases.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
See 3 more Smart Citations